Kelayakan Finansial Usahatani Kopi Arabika di Kecamatan Way Ratai Kabupaten Pesawaran - Tasmania Ayu Permata Liana; Fembriarti Erry Prasmatiwi; Zainal Abidin (Journal of Food System & Agribusiness, 2021)
The aims of this research are to analyze financial and non-financial feasibility of arabica coffee and robusta coffee farmings. The research is conducted in Way Ratai Sub-district, Pesawaran Regency in February 2020. The samples are 16 arabica coffee farmers who are selected using census method and 30 robusta coffee farmers who are selected using simple random sampling method. The analysis methods are financial and non-financial feasibility analysis includes analysis of technical, economic, social, market, and environmental aspects. The study shows that arabica coffee and robusta coffee farmings are profitable and feasible. The NPV value of arabica coffee farming is Rp358.693.372 and robusta coffee farming is Rp116.446.261. The Net B/C value of arabica coffee farming is 35,94 and robusta coffee farming is 13,32. The Gross B/C value of arabica coffee farming is 2,91 and robusta coffee farming is 1,70. The Payback Period value of arabica coffee farming is 3,90 and robusta coffee farming is 5,07. The IRR value of arabica coffee farming is 86% and robusta coffee farming is 56%, which are higher than bench mark interest rate. Arabica coffee and robusta coffee farmings are still profitable although production costs increases by 2,98%, production decreases by 17,27%, selling price of arabica coffee decreases by 12,48% and robusta coffee decreases by 18%. The study shows that both arabica coffee and robusta coffee farmings are feasible.